Property–Activity Relations for Methane Activation by Dual‐Metal Cu–Oxo Trimers in ZSM‐5 Zeolite. Issue 12 (24th August 2018) - Liu, Chong; Li, Guanna; Pidko, Evgeny A.
Abstract: The identification of correlations between the experimentally or computationally measurable parameters of a catalytic system and its reactivity is one of the key steps toward the realization of a catalysis by design strategy. Here, periodic density functional theory calculations to establish such correlations for perspective catalysts for selective methane oxidation based on dual‐metal cation‐exchanged zeolites are employed. A representative trimeric metal–oxo active site is considered as a model reactive center. Computations reveal that the activation barrier for the homolytic CH bond cleavage in methane correlates well with the thermodynamic stability of the resulting CH3 ·⋯HO intermediate. The stability of the HO part approximated by the hydrogen affinity of the active site correlates with the activity trend, but deviations are observed due to inability of this descriptor to account for the stabilization of the CH3 ∙ moiety. Such fundamental characteristics as the atomic spin density and the basicity of reactive oxygen sites cannot be directly correlated with the catalyst reactivity, implying the complexity in property–reactivity relationship for methane activation. Calculations suggest that the initial screening of the potent zeolite‐based catalyst for methane activation can be established based on the analysis of both the thermodynamics and perturbation of base molecular adsorption probes such as pyrrole. Abstract : The scaling laws in methane activation are computationally investigated using a series of dual‐metal cation‐exchanged zeolite materials. The dependendcy of the catalyst reactivity on different structural parameters such as hydrogen affinity, atomic spin density, and the basicity of active oxygen sites is explored to understand the property–reactivity relationship for methane activation.